2020
DOI: 10.7150/ijms.41354
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue-Derived Mesenchymal Stem Cells Suppress Growth of Huh7 Hepatocellular Carcinoma Cells via Interferon (IFN)-β-Mediated JAK/STAT1 Pathway in vitro

Abstract: Interferon (IFN)-β and/or tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) secreted by adipose tissue-derived mesenchymal stem cells (ASCs) have been proposed as key mechanistic factors in anti-cancer efficacy in lung cancer and breast cancer cells, where they act through paracrine signaling. We hypothesized that IFN-β and TRAIL produced by ASCs suppress proliferation of hepatocellular carcinoma cells (HCCs). The present study evaluated the anti-cancer effects of ASCs on HCCs in vitro. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…NK4 modified MSCs could inhibit the growth and migration of MHCC-97H cells and tumor angiogenesis ( 64 ). In vitro , adipose tissue-derived MSCs can inhibit the growth of Huh7 HCC cells through IFN β-mediated JAK/STAT1 pathways ( 65 ). Similarly, UCMSCs could inhibit the growth of HepG2 cells and promote their apoptosis by down-regulating AFP, Bcl-2 and Survivin ( 66 ).…”
Section: Roles Of Mesenchymal Stem Cells In Liver Cancermentioning
confidence: 99%
“…NK4 modified MSCs could inhibit the growth and migration of MHCC-97H cells and tumor angiogenesis ( 64 ). In vitro , adipose tissue-derived MSCs can inhibit the growth of Huh7 HCC cells through IFN β-mediated JAK/STAT1 pathways ( 65 ). Similarly, UCMSCs could inhibit the growth of HepG2 cells and promote their apoptosis by down-regulating AFP, Bcl-2 and Survivin ( 66 ).…”
Section: Roles Of Mesenchymal Stem Cells In Liver Cancermentioning
confidence: 99%
“…Although in vitro cellular experiments have shown that MSCs and their exosomes effectively inhibit the proliferation of hepatocellular carcinoma cell lines [ 568 570 ], which involves multiple signaling pathways [ 571 ], some evidence suggests that MSCs also promote the proliferation and progression of HCC [ 572 576 ]. The specific regulatory mechanisms regarding the promotion or suppression of tumors by MSCs remain unclear.…”
Section: Mscs For Immunocompromised Liver Diseasesmentioning
confidence: 99%
“…On the other hand, IV administration requires higher doses of MSCs to distribute over a wider area in a faster manner ( Kabat et al, 2020 ; Rady et al, 2020 ). Additionally, the timing of implantation (e.g., acute vs. delayed metastasis) is critical to enhance clinical efficacy ( Byun et al, 2020 ). When angiogenic genes are engineered into MSCs, especially if they have EPC phenotype, their transplantation serves as a viable treatment for attenuating brain inflammation and repairing the BBB ( Antonucci et al, 2011 ; Miloradovic et al, 2020 ; Pawitan et al, 2020 ; Castelli et al, 2021 ; Li et al, 2021 ).…”
Section: Stem Cell Rescue Of the Pathologic Blood-brain Barriermentioning
confidence: 99%